The judicial control of criminal execution in Brazil: ambiguities and contradictions of a perverse relationship - Patrick Cacicedo (Revista Brasileira de Direito Processual Penal, 2018)
This study aims to analyze critically the judicial control of criminal execution in Brazil. Based on three distinct aspects of criminal execution, it seeks to expose the ambiguities and contradictions of the jurisdictionalisation of the execution of sentences in Brazil, whose doctrinal debate has not gone beyond the legal nature of this field of law. In addition to the debate on the need for judicial control of criminal execution in Brazil, it is intended to point to the complexity of the issue from concrete problems that are not very much addressed by the authors of the area. Thus, the analysis of judicial control of the progressive system, the disciplinary question, as well as the rights related to the material conditions of imprisonment, reveals serious problems that the theme engenders, especially as regards the forms of management and control of prisoners, in order to contribute with the debate to a field of law that needs to be deepened scientific.